2020
DOI: 10.3390/ijerph17186604
|View full text |Cite
|
Sign up to set email alerts
|

Body Water Content and Morphological Characteristics Modify Bioimpedance Vector Patterns in Volleyball, Soccer, and Rugby Players

Abstract: Background: Bioimpedance vector analysis (BIVA) is a widely used method based on the interpretation of raw bioimpedance parameters to evaluate body composition and cellular health in athletes. However, several variables contribute to influencing BIVA patterns by militating against an optimal interpretation of the data. This study aims to explore the association of morphological characteristics with bioelectrical properties in volleyball, soccer, and rugby players. Methods: 164 athletes belonging to professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…It seems that the energy requirements of padel are closer to those reported previously for tennis [30]. Currently, Campa et al [31] developed a cross-sectional observational study on 1556 athletes, sorted into three groups: endurance, velocity-power, and team sports, obtaining similar results to ours for the velocity-power group, which included tennis.…”
Section: Discussionsupporting
confidence: 87%
“…It seems that the energy requirements of padel are closer to those reported previously for tennis [30]. Currently, Campa et al [31] developed a cross-sectional observational study on 1556 athletes, sorted into three groups: endurance, velocity-power, and team sports, obtaining similar results to ours for the velocity-power group, which included tennis.…”
Section: Discussionsupporting
confidence: 87%
“…However, in recent years, the bioimpedance vector analysis (BIVA) has been increasingly used for the assessment of body composition. BIVA is considered to be free from errors associated with prediction equations as it interprets the raw bioimpedance value resistance (R) and reactance (Xc) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the soccer player of the new millennium is an athlete who has both a high muscle mass and important physical dimensions. In addition, some studies have reported that roles such as external defender and midfielders [19], which have to cover greater distances during the match, may have a greater ectomorphic component than the mesomorphic one. In fact, better endurance characteristics can be found in ectomorphic athletes, such as runners [10].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, BIA is often used in the body composition assessment of athletes, especially soccer players [16][17][18]. Recently, it has been demonstrated that bioelectric properties are able to discriminate the different somatotype categories in athletes, given the predictive role of their raw measurements with muscle mass and body fluids distribution, which vary according to the absolute FM and FFM content [8,19,20].…”
Section: Introductionmentioning
confidence: 99%